Evaluation of Adnexal Masses-Correlation of Clinical, Sonological and Histological Findings in Adnexal Masses - Acharya, Manisha; Kumar, P; Shrestha, BB; Shrestha, S; Amatya, R; Chhetri, PB (Nepal Medical College Journal, 2020)
Adnexal mass is a common clinical finding in gynaecological practice. The study aims to find out the diagnostic value of clinical examination, ultrasonography and Ca-125 and its correlation, using Risk of Malignancy Index with histopathological diagnosis in adnexal masses. Clinical records were retrieved of women who had surgical management for adnexal mass in the last 2 years duration. Based on the data, Risk of Malignancy Index values were calculated. It was then compared with histopathological diagnosis. Out of 66 patients, 56 patients had benign tumor and 10 patients had malignancy. The Risk of Malignancy Index values of each patient was calculated which ranged from 8 to 2205 with mean value of 425.52 (SD±41.8). Risk of Malignancy Index sensitivity was 70%, specificity was 96.42%, positive predictive value was 77.78%, and negative predictive value was 95.83%. Risk of Malignancy Index is a reliable diagnostic tool in differentiating benign from malignant adnexal masses.